Science class and society - Therborn, Goran (London, 1980)
Science, Class and Society is the first systematic attempt to compare classical sociology and historical materialism the respective and rival traditions founded by Comte, Durkheim, Weber and Pareto on the one hand, and Marx and Engels on the other. Therborn starts with a critique of four major recent 'self-reflective accounts of sociology from within the modern discipline itself those of Talcott Parsons, Wright Mills, Alvin Gouldner and Robert Friedrichs. He then turns to the history of the discipline which preceded sociology-the emergent 'economics in the age of Enlightenment, and furnishes a compelling account of its material and social background, from Smith and Ricardo to Jevons to Keynes. Situated against the ascent of classical economics, sociology is interpreted as the product of a subsequent 'age between two revolutions'-a system of thought that emerged in the aftermath of the French Re w matured on the eve of the proletarian revolution in Russia, in the w of Durkheim, Weber and the 'elite theorists' from Michels to Pareto. The purpose of the new discipline of sociology, Therborn argues, was to cope with the increasing problems of class conflict and industrial unrest in Europe as the 19th century progressed towards its hour of reckoning in the First World War. Therborn locates the major intellectual achievement of this tradition in the discovery of what he calls the 'ideological community' as an object of legitimate scientific enquiry, comparable with the 'market' of classical economics. In doing so, he throws new light on the work of Durkheim and Weber in particular. The book ends with an analysis of the conditions of formation-social and theoretical-of Marxism itself. Writtem in an urbane and lively style, Science, Class and Society promises to become a classic for sociology students and readers, socialist and non-socialist alike.
On the formation of sociology and historical materialism.
Keywords: Social science